PWE-082 The art of combining clinical intuition and nuclear medicine in diagnosing bile acid malabsorption. (June 2019) - Lok, James; Peters, Mike; Mateen, Bilal; Logan, Robert
Abstract : Introduction: NICE DG7 (2012) highlights the problems of SeHCAT scanning in the diagnosis of Bile Acid Malabsorption (BAM) for patients presenting with IBS-D. 2018 BSG guidelines for the investigation of chronic diarrhoea recommend both SeHCAT scanning (for the diagnosis of BAM) and colonoscopy (for diagnosis of microscopic colitis), which can occur in up to 25% and 10% of cases of IBS-D, respectively. Nocturnal symptoms and incontinence are 'hallmark' symptoms for microscopic colitis. This retrospective study evaluates the use of SeHCAT scanning at a London teaching hospital and explores if similar 'hallmarks' exist for BAM. Methods: The patient cohort was identified by searching the CRIS database from inception to Oct 2018 whilst clinical data was extracted from the electronic patient record system. SeHCAT scans were performed using 75 Se-hemoefolic acid taurine capsules at a dose of 0.4MBq and 0.3mSv. Gamma counts were recorded 3 hours and then 7 days post capsule administration using a camera detecting the 27–80keV photo peak and retentions of <15% were considered abnormal. Data collected included demographics, clinical presentation (abdominal pain, diarrhoea, bloating, incontinence, urgency, nocturnal symptoms) and relevant past medical history. Multivariate analysis of symptoms was performed using a generalised linear model with elastic net and K fold cross validation. Patients with terminal ileal resections or IBD were excluded from subsequent analysis. Results: From Jan 2013 to Oct 2018, 524 patients underwent a SeHCAT scan (65% female, mean age 51) and the rate of testing increased sequentially from 26 per annum to 124 per annum over five years. Detailed statistical analysis of symptom cluster failed to identify any 'hallmark', but nevertheless 49.8% of patients had abnormal tests, 56.7% of which were requested by 4/16 consultant gastroenterologists. Sixty-four patients developed diarrhoea following a laparoscopic cholecystectomy (n=2476) of whom 41 (64%) had positive scans. In the same time period as this study, 1719 patients underwent colonoscopy and biopsy due to unexplained diarrhoea. Conclusions: These data confirm that BAM is common but is under-investigated in comparison with microscopic colitis. Although it is not associated with any 'hallmark' symptoms, it is readily identified by experienced clinicians as suggested by the high pick up rate, presumably on the basis of clinical acumen. It occurs in approximately 2% of patients following cholecystectomy, although the true prevalence in this population may be greater. These data also support the BSG guideline audit recommendation of SeHCAT in IBS-D as a quality improvement target.